CORRELATION OF QUALITY HEALTH SERVICES AND THE MOTIVATION OF PATIENTS REVISITING POLYCLINIC - Haniwijaya Tjokro, Silvia; Mamesah, Marline (jfpublisher, 2022)
Introduction. The hospital as an institution that provides health services has the same responsibility as other health care institutions to improve the health status of the community. Health problems have become a basic need for society. The increase in the standard of living of the community, makes the demands of the community on the quality of health services also increase. The purpose of this study was to analyze correlation of quality health services and the motivation of patients revisiting polyclinic. Methods. The research design used in this study was a descriptive research design with a cross sectional approach. Population was patients who attend Polyclinic of Adi Husada Kapasari Hospital during the research. Sample size in this research were 24 respondents, using the Simple Random Sampling technique. Data analysis used Spearman Rho test. Results & Analysis. Results obtained higher service quality in the category of Enough as many as 14 people (58%), motivation to visit the polyclinic is higher in the Good category as many as 12 people (50%). The results of the Spearman test showed that there was a relationship between service quality and motivation to return to the polyclinic (p value = 0.000 <0.05). Discussion.It is hoped that hospitals should evaluate the quality of health services periodically to ensure whether the quality of health services provided by health workers is consistent and in accordance with hospital standards.